PEMAHAMAN GURU TERHADAP KONSEP PENDIDIKAN KARAKTER DI SMP KABUPATEN MUSI BANYUASIN - Yustriani, Yustriani; Yusnarni, Yusnarni (Graduate Program Magister Manajemen Pendidikan, 2018)
Character education in SMP Negeri 2 Babat Supat has already been integrated in the curriculum in every subject, but on the other hand the teachersâ understanding and mastery of the concept of character education needs to be reviewed further, the teachers did not understand the nature of the concept of character education. The content of character values found in learning during the learning activities include: 1) Religious, 2) Honest, 3) Tolerance, 4) Discipline, 5) Hard work, 6) Creative, 7) Independent, 8) Democratic , 9) The Want to Know, 10) The Spirit of Nationality, 11) The Love of the Homeland, 12) Respect for Achievement, 13) Friendly / Communicative, 14) Peaceful Love, 15) Love Reading, 16) Environmental Care, 17) Social Care, and 18) Responsibility. This qualitative research investigate the understanding of teachers to the concept of character education. Lack of deep understanding of a teacher on the concept of character education will inhibit the implemention to the learners, so it needs to be held again coaching or training of teachers and employees in SMP Negeri 2 Babat Supat.